Entrepreneurial Intention: The Moderating Role of Improvisation on Student Faculty of Economics, State University of Malang - Desi Anggrianto -; Ery Tri Djatmika; Wening Patmi Rahayu (Journal of Business and Management Review, 2021)
Scholars and students are believed to be capable of becoming educated entrepreneurs and opening job vacancies to overcome unemployment. This research was carried out to investigate the entrepreneurial intention of students of the Faculty of Economics, Universitas Negeri Malang, in which the entrepreneurial intention is the closest to the act of entrepreneurship. This research is a quantitative study using analysis techniques hierarchical regression. The results showed that entrepreneurial intention was influenced by self-efficacy and improvisation, while personality and subjective norms did not affect the entrepreneurial intention. The interaction relationship between self-efficacy and improvisation affected negatively on entrepreneurial intentions. Male students were found to have higher entrepreneurial intentions than women.